Perbedaan Prestasi Belajar Siswa Melalui Pembelajaran Daring Menggunakan Aplikasi Whatsapp Group dan Google Classroom - Nurul Khotizah; Nani Kurniati; Sripatmi Sripatmi; Syahrul Azmi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to determine the difference in learning achievement of class VIII students of SMP Negeri 4 Mataram through online learning using the WhatsApp Group and Google Classroom applications for the 2020/2021 academic year. This research is an experimental study with a posttest-only non-equivalent group design used . Determination of the sample using probability sampling technique with the sample being class VIII 2 students receiving online learning using the WhatsApp Group application as an experimental class 1 and class VIII 3 students receiving online learning using the Google Classroom application as an experimental class 2. The instrument used in this study was an instrument The test is in the form of a post-test on the Pythagorean theorem and constructing flat-sided spaces. Data analysis was used using t-test. The results showed that there was no difference in learning achievement between students who received online learning using the Whatsapp Group and Google Classroom applications.